2014
DOI: 10.3109/15563650.2014.969371
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac conduction disturbance after loperamide abuse

Abstract: This case series describes several patients with cardiac conduction abnormalities and life-threatening ventricular arrhythmias temporally related to loperamide abuse. With the recent efforts to restrict the diversion of prescription opioids, increasing abuse of loperamide as an opioid substitute may be seen. Toxicologists should be aware of these risks and we urge all clinicians to report such cases to FDA Medwatch(®).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 4 publications
0
79
0
Order By: Relevance
“…The patient had a structurally normal heart, and literature review confirmed identical presentations associated with loperamide overdose. While other aforementioned electrocardiographic abnormalities have been described in scant case reports [3][4][5], to our knowledge, this is the first case report of this agent unmasking a Brugada pattern. Previous reports describe markedly elevated serum loperamide concentrations with presentations including life-threatening ventricular tachyarrhythmias, and varying degrees of QRS and QTc prolongation.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The patient had a structurally normal heart, and literature review confirmed identical presentations associated with loperamide overdose. While other aforementioned electrocardiographic abnormalities have been described in scant case reports [3][4][5], to our knowledge, this is the first case report of this agent unmasking a Brugada pattern. Previous reports describe markedly elevated serum loperamide concentrations with presentations including life-threatening ventricular tachyarrhythmias, and varying degrees of QRS and QTc prolongation.…”
Section: Discussionmentioning
confidence: 90%
“…Marraffa et al [3] 26 y/o PMH opioid abuse. Recurrent syncope, TdP requiring cardioversion, QTc>700 ms 100-150 mg loperamide with 400 mg cimetidine daily for 7 days Started on isoproterenol infusion initially.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An overdrive pacemaker was used to achieve the same strategy. Lidocaine was added to stabilize the ventricular membrane [14,15]. After the initial usage during a VF arrest, amiodarone use was avoided because of the risk of QT prolongation.…”
Section: Discussionmentioning
confidence: 99%